The connection between teaching and learning: Linking teaching quality and metacognitive strategy use in primary school. (18th July 2016) - Rieser, Svenja; Naumann, Alexander; Decristan, Jasmin; Fauth, Benjamin; Klieme, Eckhard; Büttner, Gerhard
Abstract : Background: In order for teaching to be successful, students need to be actively involved in learning. However, research on teaching effectiveness often neglects students' learning activities. Although it is assumed that effective teaching promotes the use of beneficial learning activities, empirical evidence for this connection is still limited. Aims: This study aimed to investigate the connection between effective teaching and reported learning activities. We hypothesize specific relations between a three‐dimensional model of teaching quality (i.e., cognitive activation, supportive climate, and classroom management) and students' reported use of metacognitive strategies. Students' intrinsic motivation is considered as a mediator and a moderator of this connection. Sample: N = 1, 052 students from 53 German primary school classes and their science teachers participated. Methods: Data were collected through classroom or video observation and questionnaires over a period of approximately 2 months. Multilevel analysis was utilized to test our hypotheses. Results: Each dimension of teaching quality positively predicted students' reported use of metacognitive strategies. For supportive climate, this connection was mediated by students' intrinsic motivation. Cognitive activation negatively predicted the slopes between students' reported metacognitive strategy use and motivation. Conclusions: The results support the notion that effective teaching is connected to learning activities and stress the importance of students' learning motivation. Results from the cross‐level interaction could indicate that especially less motivated students' reported metacognitive strategy use might be supported by cognitively activating teaching.